ANALYSIS OF ECONOMIC GROWTH AND SHIFTING FIELD SECTOR EFFORTS IN THE CITY OF MAKASSAR - Hukma Ratu Purnama (Indonesia Prime, 2016)
This research aims to know the influence of the shift towards growth sectors GRP Makassar city and to know the dominant business field sector affect economic growth (GDP) in the city of Makassar. The analysis of the data used is shift share analysis assumes that the growth of a region can be divided in three components of the factor. The results of this research show that the sector of the field the most superior in the city of Makassar trading sector is where the sector contributes the largest economy in the city of Makassar.